4х-5=7;
4х=12;
х=3;
Ответ: 3
3х - у = 3 ⇒ у= -3+3х
5х + 2у = 16 5х+2у=16
5х + 2(-3+3х) = 16
5х - 6 + 6х = 16 у = -3 + 3*2
11х = 22 у=3
х=2
Ответ: (2;3)
3 - (х-2у)-4у=18 ⇒ 3-х+2у-4у=18 ⇒ -х-2у=15 ⇒ х+2у=-15
2х-3у+3=2(3х-у) 2х-3у+3=6х-2у -4х-у=-3 4х+у=3
х+2у=-15
у=3-4х
х+2(3-4х)=-15 у=3-4*3
х+6-8х=-15 у= -9
-7х=-21
-х=3
х=3
Ответ (3; -9)
<span>2x>-4 x>-2 делим на положительное число знак неравенства не меняется
5x<-3</span> x<-3/5
-2<x<-3/5
система:
а+в=14;
10в+а=10а+в-18;
а+в=14; приплюсуем оба уравнения
в-а=2;
2в=16
в=8
а=6